Hemangiomas cervicales. Descripción de cuatro casos - Torres Morientes, Luis M. (2016)
Introduction and objective: The hemangioma is a tumor that consists of dilation and thickening of capillary loops. Most ot these tumors are present at birth or little bit later and they are the most common tumors in the pediatric population. 60% of all of them are located in head and neck. In neck they show soft consistency without pain. Case description: We report four cases of cervical hemangiomas seen in our department in one year. They were located in the external yugular vein, the submaxilar gland and at submucosal hypopharyngeal and cervical posterior level. Discussion: Hemangiomas have an unknown etiology and they are located in any anatomic location although the highest prevalence is in head and neck. The differential diagnosis include vascular phlebectasias, branchial cysts, laryngoceles and lymphangiomas. The treatment of choice goes from conservative measures to surgical excision due to rapid growth or aesthetic reasons. Conclusions: Hemangiomas must be included in the differential diagnosis of cervical tumors. They are frecuently confused with vascular phlebectasias. Treatment is usually the surgical resection.